Program Siaran Interaktif (Talk Back Radio) Sebagai Ruang Publik Masyarakat Untuk Mengembangkan Demokrasi Lokal: Studi Pada Program ”Citra Publika” Radio Citra 87,9 FM Kota Malang - Rochmad Effendy (Program Studi Ilmu Komunikasi, 2014)
As social institution, national press should serve pubic interest by meeting the people’s right to know in the form of news which concerns the lives of the people. In addition to that, press is also required to serve public to spare its pace and time for people to express their voices and grievances regarding public issues. Due to its interactivity and hyper-local journalism, radio can perform this well. Talkback radio broadcasts containing interaction between the host broadcaster with the listener expressing their concerns and information on public issues have been able to encourage the process of local democratization. As such “Citra Publika